Lack of evidence for a liver or intestinal miRNA regulation involved in the hypertriglyceridemic effect of APOC3 3′UTR variant SstI. (December 2016) - Dancer, Marine; Caussy, Cyrielle; Di Filippo, Mathilde; Moulin, Philippe; Marçais, Christophe; Charrière, Sybil
Abstract: Background and aims: APOC 3 is a major regulator of triglycerides metabolism. Several APOC 3 variants are associated with hypertriglyceridemia (HTG). Our aim was to establish the potential regulation of APOC 3 3′UTR variants associated with HTG by liver or intestinal miRNAs. Methods: We sequenced APOC 3 3′UTR in 100 type 2 diabetic (TD2) patients with severe HTG (TG > 15 mmol/L) (HTG group) compared to 100 normotriglyceridemic patients (NTG group). We performed in silico studies to identify potential loss of miRNA binding induced by APOC 3 3′UTR variants. We also performed in vitro studies to test the functionality of miRNA/ APOC 3 variants interactions: APOC 3 3′UTR plasmids coupled with a firefly luciferase reporter were transfected in HepG2, HuH-7 and Caco-2 cells. Results: We identified only two variants: SstI (rs5128) and BbvI (rs5225) in APOC 3 3′UTR in the 2 groups of patients. Only the SstI-S2 rare allele was significantly associated with HTG (allele frequency 19, 5% in HTG group vs. 9, 5% in NTG group, p  = 0.0045). In silico studies predicted a potential loss in the binding of 5 miRNAs induced by the S2 variant. These 5 miRNAs are all endogenously expressed in human liver and intestine, as well as in the cell models studied. However, in vitro, the S2 variant did not modulate APOC 3 3′UTR reporter gene expression in HepG2, HuH-7 and Caco-2 cells. Conclusions: Our results do not confirm the hypothesis of a direct regulation of the APOC 3 SstI variant by hepatic or intestinal miRNAs. Highlights: Several APOC 3 variants are associated with hypertriglyceridemia. SstI APOC 3 3′UTR variant is associated with severe hypertriglyceridemia (HTG) in our cohort. APOC 3 3′UTR variants could be regulated by liver or intestinal miRNAs. Our results do not confirm a direct miRNA regulation in presence of the SstI variant.